Major Kinds of Drug Targets in Chagas Disease or American Trypanosomiasis - Duschak, Vilma G (2019)
Fil: Duschak, Vilma G. ANLIS Dr. C. G. Malbrán. Instituto Nacional de Parasitología Dr. Mario Fatala Chaben; Argentina.